Pengaruh dari Pembelajaran Daring Terhadap Pengelolaan Pendidikan Di SD - Auli Ihza Ahyati; Reska Widyaksana Nugraha; Rindi Rendiyawati; Husen Windayana (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2022)
The COVID-19 pandemic has had an impact on several sectors, sectors that have experienced the greatest impact, namely the economy and education, where education during the COVID-19 pandemic was conducted online (in a network). The progress of education is strengthened by the statement of the 2003 Law system and the 2005 government regulation regarding national education standards, then the basic education level must contain several aspects, namely: curriculum content, graduates or educational success, learning process, educators and teaching staff, education costs and education system What is needed The implementation of online learning has been stipulated in government regulations, with online learning this will certainly change the system or concept of learning used. The existence of this management helps schools in regulating the concept of learning and the education system which is of course done in a structured manner. Management of education is considered very important in achieving educational goals. This research is motivated by the influence of online learning on the management of education in elementary schools, where it can be seen that the covid 19 pandemic that affects the learning system will have an impact on the management of education. This study uses a qualitative survey literature methodology, where the discussion is reviewed through the results of surveys that have been conducted on educators and students, then the survey results obtained are strengthened by the opinions of experts who have been quoted through journals. This study also aims to see the effect of online learning on the planning, implementation, supervision and management of education in elementary schools. The results of this study are that the management of educators affects the learning methods used. The existence of this article is hopefully able to see and review the implementation of education management in elementary schools whether it is appropriate or not and review the influence of online learning.